Microbial and composition changes during vermicomposting process resulting from decomposable domestic waste, cow manure and dewatered sludge - Iman Parseh; Keyvan Mousavi; Ahmad Badieenejad; Mohammad Mehdi Golbini Mofrad; Majid Hashemi; Omid Azadbakht; Hosein Karimi (International Journal of Environmental Health Engineering, 2021)
Aim: Although vermicomposting is rich in nutrients, the virulent microbes and pathogens present in it may be a threat to human health and the environment. Therefore, the objective of this study is to investigate the microbial quality of produced vermicompost, including fecal coliform and parasitic eggs, at a pilot scale, and compare it to present standards. Materials and Methods: Three various reactors containing decomposable domestic waste (T1), cow manure (T2), and dewatered sludge (T3) were used to produce vermicompost using Eisenia fetida. According to the standard methods, fecal coliforms, parasitic eggs, and some of the treatment characteristics including organic carbons, nitrogen, temperature, humidity, pH, electrical conductivity and metals were evaluated during the 56-day operation period. Results: According to the results, the number of fecal coliforms in treatments of T1, T2 and T3 reduced from 2.5 × 104, 6 × 105 and 15 × 106 to 1000, 1500 and 1500 MPN/g dw, respectively. All parasite eggs reached zero after the 3rd week. At the end of the study, the average of organic carbon in T1, T2, and T3 were 35.4 ± 6%, 50.7 ± 5%, and 58.4 ± 7%, respectively. This value for total nitrogen were 0.9 ± 0.2%, 1.8 ± 0.7%, and 4.2 ± 1.2%, respectively. Conclusion: Results showed that the worm E. fetida has a great ability to reduce pathogens without the need for an increase in temperature. Furthermore, it can be concluded that vermicompost can improve the quality of compost in 8 weeks. The vermicomposting process can also greatly destroy the fecal coliforms and all parasite eggs.